AUTOMATIC HATHING MACHINE WITH CAPABILITY EMBRIO QUALITY DETECTION OF EGGS USING REGIONPROPS AND BINARY SEGMENTATION METHOD - Rahmat Abdurrahim Sumim; Tolangowati Olii (Politeknik Negeri Bandung, 2018)
Abstract— This study is making a system that combines two system from egg hatching machine and egg embryo quality detector into one tool. So it can facilitate the breeder in sorting the damaged egg or infertile during the hatching process. The eggs used in this research are kampong chicken eggs. The method used in egg identification process is using binary segmentation and regionprops method. Combining those two methods can maximize the detection of egg embryo with the number of eggs more than one to detect, so it can increase the efficient of hatching egg. The identification based on the value of pixel from the embryo image. Each egg will give a certain pixel value, and this becomes a benchmark in determining the quality of the egg. In the egg hatch machine there is a temperature control system using PID method and ON-OFF control system for humidity control. The final result from this research is making a tool of combination from two systems, which is egg hatcher machine and also egg embryo quality detection.